Distributive characteristics of subject-objective adverbial predicates of the state (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The flow diagrams of the sentences organized subject-objective adverbial predicates of the state are analysed in the article, subject and objective components of such syntactic structures, obligatory and optional distribution of adverbial predicates of the state within the limits of the given models.
Keywords: adverbial spreader; model of sentence; object; predicate; subject; optional distribution